Equity in the Evidence Base: Demographic Sampling in Intervention Research for Students With Emotional and Behavior Disorders. (November 2017) - Carrero, Kelly M.; Collins, Lauren W.; Lusk, Mandy E.
Researchers have been working diligently to build the evidence base for what works for youth with emotional and behavioral disorders (EBD). As the evidence base grows, the field must investigate what works, for whom, and under what conditions. To begin to address for whom the mounting evidence is applicable, this study systematically reviewed demographic sampling in 22 intervention studies investigating six instructional practices that target academic outcomes (i.e., classroom-wide peer tutoring, increased opportunities to respond, peer-assisted learning strategies, self-monitoring, pre-correction, and direct/explicit instruction) for students receiving services for emotional disturbance and at-risk for EBD published from 2005 to 2015. Results indicated complete absence of American Indian/Alaska Native, Native Hawaiian/Other Pacific Islander, and Two or More Races in these studies. Asian participants and Hispanic/Latino participants are also underrepresented. There is little disparity in gender distribution when participants are compared with national-level data. Implications include considering how students with EBD from diverse backgrounds are recruited for and reported in academic intervention research.